Studi Kasus Asuhan Gizi Pada Pasen Stroke Hemipareses Dekstra di Rumah Sakit Khusus Daerah Dadi Propinsi Sulawsei Selatan - Abdullah Tamrin; Hendrayati Hendrayati; Hadrawati Hadrawati (Jurusan Gizi Poltekkes Kemenkes Makassar, 2020)
AbstractBasic health research conducted by the Ministry of Health of the Republic of Indonesia in 2013 reported that in Indonesia there were more than 2 million inhabitants, or 12 out of 1000 population, suffering from strokes with the largest percentage coming from the province of South Sulawesi. Stroke is the number 1 killer in Indonesia, more than 15% of deaths in Indonesia are caused by stroke. Incorrect nutrition care is a factor that can cause a stroke. Consumption of saturated fats such as butter, biscuits, meat products, biscuits and cream can increase the incidence of stroke which is mediated by an increase in blood pressure. High cholesterol consumption will cause arteries to narrow and can clog blood circulation in the atherosclerosis body is a risk factor for stroke. This case study describes nutritional care at the Passive Hemipareses Stroke patient at the Dadi Special Hospital in South Sulawsei Province, for five days of observation. Observations were carried out for 5 consecutive days. Indicators that are evaluated for intake levels using sesilisih complete food and leftover food items, data from laboratory examination results and clinical physical examination results are taken secondary from the medical record of the patient.The observation shows that the NCP implementation process in this case can run and the pasent undergoes changes that lead to improvement.The results of the study recommend monitoring and evaluating the level of patient consumption carried out for each meal to determine the state of the patient, so as to determine the development of the diet, and intake from outside the hospital. Keywords: Intake level ,Nutrition Care, Stroke, ,